Accessing Health Information and Health Services - Rita Araújo; Julia C. M. van Weert (University of Zurich, IKMZ - Department of Communication and Media Research, 2024)
European health communication is rich and diverse in terms of international perspectives, scientific approaches and topics. The ECREA Aarhus Best Papers special issue showcases this diversity. It features the best papers presented at the health communication section of the ECREA conference, which took place in Aarhus in 2022. Four papers were selected for publication through a comprehensive evaluation procedure.